Wind effects on rough-walled and smooth-walled large cooling towers. Issue 6 (June 2017) - Cheng, XX; Zhao, L; Ge, YJ; Dong, R; Demartino, C
Adding vertical ribs is recognized as a useful practice for reducing wind effects on cooling towers. However, ribs are rarely used on cooling towers in China since Chinese Codes are insufficient to support the design of rough-walled cooling towers, and an "understanding" hampers the use of ribs, which thinks that increased surface roughness has limited effects on the maximum internal forces that control the structural design. To this end, wind tunnel model tests in both uniform flow field with negligible free-stream turbulence and atmospheric boundary layer (ABL) turbulent flow field are carried out in this article to meticulously study and quantify the surface roughness effects on both static and dynamic wind loads for the purpose of improving Chinese Codes first. Subsequently, a further step is taken to obtain wind effects on a full-scale large cooling tower at a high Re, which are employed to validate the results obtained in the wind tunnel. Finally, the veracity of the model test results is discussed by investigating the Reynolds number (Re) effects on them. It has been proved that the model test results for atmospheric boundary layer flow field are all obtained in the range of Re-independence and the conclusions drawn from model tests and full-scale measurements basically agree, so most model test results presented in this article can be directly applied to the full-scale condition without corrections.